Perceptual Development and Auditory Backward Recognition Masking - Massaro, Dominic W; Burke, Deborah (Developmental psychology, 1991)
In three amplitude discrimination experiments involving a backward masking task, children's rate of perceptual processing was compared to that of adults. Developmental differences in discrimination were compensated for by increases in the psychophysical difference between test tones. No developmental differences in rate of perceptual processing were observed. (BC)